Entry routes into the Institute of Chartered Accountants of Scotland training: Status versus sustainability. (February 2018) - Gammie, Elizabeth; Allison, Mark; Matson, Morag
Education plays a pivotal role in establishing the elite status of a profession. This article sets out to understand the role of social and political influences in the determination of entry routes to professional accounting training with the Institute of Chartered Accountants of Scotland (ICAS). The article charts the development of various entry routes which converted ICAS from an Institute with few graduate entrants in the mid-1950s to an Institute with almost 100 per cent graduate entrants today.